2019
DOI: 10.1186/s41205-019-0039-x
|View full text |Cite
|
Sign up to set email alerts
|

Low cost additive manufacturing of microneedle masters

Abstract: Purpose Microneedle patches are arrays of tiny needles that painlessly pierce the skin to deliver medication into the body. Biocompatible microneedles are usually fabricated via molding of a master structure. Microfabrication techniques used for fabricating these master structures are costly, time intensive, and require extensive expertise to control the structure’s geometry of the structure, despite evidence that microneedle geometry is a key design parameter. Here, a commercially available 3D pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 22 publications
1
54
0
Order By: Relevance
“…These hollow microneedle interfaces enable transdermal drug delivery through a “poke-and-flow” mode of operation, 32 where the tip creates micropores in the skin, followed by the delivery of fluids flowing through the hollow microneedle bore. The printed geometries included two of the most commonly reported 3D-printed microneedle designs: a pyramidal microneedle with a triangular base and tip orthogonally aligned with a vertex of the base, 33,34 and a conical microneedle with tapered sidewalls 35–37 . In Figs.…”
Section: Resultsmentioning
confidence: 99%
“…These hollow microneedle interfaces enable transdermal drug delivery through a “poke-and-flow” mode of operation, 32 where the tip creates micropores in the skin, followed by the delivery of fluids flowing through the hollow microneedle bore. The printed geometries included two of the most commonly reported 3D-printed microneedle designs: a pyramidal microneedle with a triangular base and tip orthogonally aligned with a vertex of the base, 33,34 and a conical microneedle with tapered sidewalls 35–37 . In Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, data in the above studies have consistently shown that microneedles allow for higher efficacy, lymphatic uptake, or lymphatic retention compared to controls. This form of drug delivery may be cost prohibitive, and scale-up can be difficult; however, newer, easier methods for microneedle fabrication are currently being researched as potential, cost-effective alternatives [178,179].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Furthermore, side effects in normal tissues and organs associated with systemic circulation can be remarkably reduced. The development of emerging microneedle manufacturing methods would enable more flexibility in the design of individualized microneedles according to the characteristics of the lesion site 42 - 44 . Also, various materials can be selected to prepare functionalized microneedles.…”
Section: Introductionmentioning
confidence: 99%